Insulation heat conduction enhanced liquid crystal epoxy and preparation method thereof

By introducing NTCDA-doped thin film materials into liquid crystal epoxy to form electron donor receptor composites, the problem of insufficient thermal conductivity and heat resistance of traditional epoxy resins is solved, and efficient heat transfer and high-temperature insulation performance is achieved.

CN119859532APending Publication Date: 2025-04-22XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510021649.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Traditional epoxy resins lack thermal conductivity and heat resistance in the fields of silicon carbide, gallium nitride and high-voltage and high-power IGBT potting, and high-content inorganic fillers lead to problems such as increasing material viscosity, increasing defects, and electric field distortion.

Method used

By introducing thin film materials BAE-x or BGE-x, where x represents the doping amount of NTCDA, NTCDA forms an electron donor acceptor complex with the liquid crystal epoxy matrix, and the conjugation effect and crystal inducing effect of NTCDA are used to improve the thermal conductivity and insulation characteristics of the material.

Benefits of technology

It significantly improves the thermal conductivity of liquid crystal epoxy and insulating properties at high temperatures, enhances the heat resistance and stability of the material, and is suitable for the design and development of high-performance electronic potting materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859532A_ABST
    Figure CN119859532A_ABST
Patent Text Reader

Abstract

The invention discloses insulation heat conduction enhanced liquid crystal epoxy and a preparation method thereof, and relates to the technical field of liquid crystal epoxy. According to the insulating heat conduction enhanced liquid crystal epoxy and the preparation method thereof, a thin film is arranged in the liquid crystal epoxy; the thin film comprises any one of BAE-x or BGE-x, and x represents the doping amount of NTCDA; the liquid crystal epoxy matrix and the NTCDA generate charge transfer interaction and form an electron donor-acceptor compound. Through the strong conjugation effect and the electron donor-acceptor effect between the NTCDA and the liquid crystal epoxy matrix, a large number of liquid crystal domains can be induced by the trace NTCDA, which is just benefited from the large number of liquid crystal domains generated by the crystal inducing effect of the NTCDA, phonons are rapidly conducted in the liquid crystal domains formed by polymer orientation and hardly scattered, so that the heat energy transfer efficiency is improved, and the service life of the liquid crystal epoxy matrix is prolonged. The heat conductivity of the material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid crystal epoxy, in particular to an insulation and thermal conductivity enhanced liquid crystal epoxy and a preparation method thereof. Background Art

[0002] The low thermal conductivity and heat resistance of traditional epoxy resins have limited their application in the field of silicon carbide, gallium nitride and future high-voltage and high-power IGBT potting. In terms of improving the thermal conductivity of epoxy, filling a large amount of high thermal conductivity inorganic fillers into the epoxy matrix is ​​currently a common method to obtain high thermal conductivity epoxy materials, but high content of inorganic fillers can easily cause problems such as increased viscosity of the potting material, increased defects, and electric field distortion, resulting in the improvement of thermal conductivity often at the expense of its insulation performance. In order to obtain high-performance polymers for power device potting, constructing a multi-scale ordered structure through molecular chain structure design is the key to solving the mutual constraints of material thermal conductivity, insulation and heat resistance. Therefore, the research on liquid crystal epoxy resin (LCE) with the ordered characteristics of π-π stacking of crystal-forming units has received widespread attention. Although LCE has synergistically improved the electrothermal performance of IGBT potting materials, the following problems still exist:

[0003] Although all-organic LCE has achieved an improvement in thermal conductivity, the improved thermal conductivity still cannot meet the thermal conductivity requirements of future high-voltage and high-power IGBTs.

[0004] Although LCE has greatly improved the breakdown field strength (BDS) at room temperature, in the extremely high temperature application environment of IGBT, when the dielectric operating temperature is 180°C, the BDS at high temperature is still reduced by about 30% relative to that at room temperature. This is unacceptable in future high-performance power device applications.

[0005] The present invention aims to fully organically modify LCE through molecular fillers that have both liquid crystal induced effect and molecular semiconductor effect, further improve the thermal conductivity of the material, and solve the problem of reduced insulation properties at high temperatures. This will help improve the reliability and stability of high-power IGBT devices, thereby promoting their performance and efficiency in extreme environments. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides an insulating and thermally conductive enhanced liquid crystal epoxy and a preparation method thereof, which solves the problems raised in the above background technology.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: an insulating and thermally conductive enhanced liquid crystal epoxy and a preparation method thereof, comprising: a liquid crystal epoxy, wherein a thin film is arranged inside the liquid crystal epoxy;

[0008] The film comprises: any one of BAE-x and BGE-x films, wherein x represents the doping amount of NTCDA;

[0009] The liquid crystal epoxy matrix generates a charge transfer interaction with NTCDA and forms an electron donor-acceptor complex.

[0010] A further improvement of the technical solution of the present invention is that the value of x in the BAE-x or BGE-x includes any one of 0%, 0.1%, 0.4%, 0.7% and 1%.

[0011] A further improvement of the technical solution of the present invention is that the BAE-x is specifically a compound of BAE and NTCDA, and the BGE-x is specifically a compound of BGE and NTCDA.

[0012] A further improvement of the technical solution of the present invention is that the present invention also provides a method for preparing an insulating and thermally conductive enhanced liquid crystal epoxy, comprising the following specific steps:

[0013] S1: Add the corresponding mass of NTCDA to 0.074g BGE or 0.166g BAE and sonicate, add 0.5g TMBP to the uniformly dispersed solvent, heat to 110°C, make TMBP completely molten and stir rapidly for 5 minutes;

[0014] S2: Add 0.165g TMB, heat to 170℃, maintain the temperature and stir rapidly for 3 minutes, place the molten liquid in a vacuum box at 140℃ for degassing for 5 minutes, then inject it into the mold and place it in a drying oven for curing. The first stage is cured at 140℃ for 4h, the second stage is heated to 180℃ for curing for 4h, and the final stage is heated to 200℃ for curing for 2h.

[0015] A further improvement of the technical solution of the present invention is that the BGE system in S1 is ultrasonicated at room temperature.

[0016] A further improvement of the technical solution of the present invention is that the BAE system in S1 is ultrasonicated at 70°C.

[0017] Beneficial Effects

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: through the strong conjugation effect and electron donor-acceptor interaction between NTCDA and the liquid crystal epoxy matrix, a trace amount of NTCDA can induce a large number of liquid crystal domains. Thanks to the large number of liquid crystal domains generated by the inducing effect of NTCDA, phonons are quickly conducted in the liquid crystal domains formed by the polymer orientation without scattering, thereby improving the efficiency of heat energy transfer and greatly improving the thermal conductivity of the material, providing new ideas and methods for the modification of liquid crystal epoxy, and is expected to open up new paths for the design and development of high-performance electronic potting materials in the future.

[0019] In addition, adding extremely low levels of NTCDA helps to improve the BDS of liquid crystal epoxy. The introduction of the NTCDA strategy captures high-energy electrons by constructing an energy band difference, effectively delaying the occurrence of electrical breakdown. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The cross-linking principle of liquid crystal epoxy matrix and the liquid crystal induction mechanism and liquid crystal domain morphology of NTCDA;

[0021] Figure 2 The following are the color development reaction of NTCDA in the liquid crystal matrix, the electronic transition diagram of NTCDA, TMBP and TMB, the fluorescence emission spectrum that proves the formation of EDA, and the fluorescence characteristic diagram of BGE-0 and BGE-1 films under 395nm wavelength excitation;

[0022] Figure 3 They are the RDF of the cross-linked models of BGE-0 and BGE-1 at room temperature and the RDF of the cross-linked models of BGE-0 and BGE-1 at 473K;

[0023] Figure 4 They are biphenyl-biphenyl conjugate adsorption model, biphenyl-naphthalene conjugate adsorption model, simulation results of molecular distance between crystallogenic units and conjugate adsorption energy, WAXS spectra of BGE-0 and BGE-1, WAXS 3D image of BGE-0, and WAXS 3D image of BGE-1.

[0024] Figure 5 The following are the breakdown Weibull distribution of BGE-x, the breakdown Weibull distribution of BAE-x, the BDS change of BAE / BGE-x, and the free volume parameter bar chart comparison of BGE-0, BGE-1, BAE-0 and BAE-1 cross-linking models;

[0025] Figure 6 They are, in order, the Weibull distribution of BDS during the heating process of BGE-0, the Weibull distribution of BDS during the heating process of BGE-0.1, the Weibull distribution of BDS during the heating process of BGE-0.4, the Weibull distribution of BDS during the heating process of BGE-0.7, the Weibull distribution of BDS during the heating process of BGE-1, a bar chart comparing BDS of BGE-x at 30°C and 200°C, the Weibull distribution of BDS during the heating process of BAE-0, the Weibull distribution of BDS during the heating process of BAE-0.1, the Weibull distribution of BDS during the heating process of BAE-0.4, the Weibull distribution of BDS during the heating process of BAE-0.7, the Weibull distribution of BDS during the heating process of BAE-1, and a bar chart comparing BDS of BAE-x at 30°C and 200°C;

[0026] Figure 7 They are the DSC curves of BAE-0 and BAE-0.7 samples, Tg simulation diagrams of BAE-0 and BAE-0.7 models, DSC curves of BGE-0 and BGE-0.7 samples, Tg simulation diagrams of BGE-0 and BGE-0.7 models, thermal conductivity characterization of BAE-x, thermal conductivity characterization of BGE-x;

[0027] Figure 8 The TSDC experimental data and fitting curve of BGE-0, and the TSDC experimental data and fitting curve of BGE-0.7 are shown in order;

[0028] Fig. 9 They are the frequency response diagrams of εr and tanδ of BAE-x, and the frequency response diagrams of εr and tanδ of BGE-x respectively. DETAILED DESCRIPTION

[0029] Various exemplary embodiments, features and aspects of the present application will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0030] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0031] In addition, in order to better illustrate the present application, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In some examples, methods, means, and elements well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present application.

[0032] Embodiment 1, the present invention provides an insulating and heat-conducting enhanced liquid crystal epoxy, comprising: a liquid crystal epoxy, wherein a thin film is arranged inside the liquid crystal epoxy;

[0033] The film comprises: any one of BAE-x and BGE-x, wherein x represents the doping amount of NTCDA;

[0034] The liquid crystal epoxy matrix and NTCDA generate charge transfer interactions and form an electron donor acceptor complex (EDA).

[0035] In this application, the charge transfer interaction between NTCDA and the liquid crystal epoxy matrix forms an electron donor acceptor complex (EDA), which increases the intermolecular force. At the same time, NTCDA has a stronger conjugation effect. The synergistic effect of charge transfer and conjugated bond energy enhances the orderliness of the molecular chain, which ultimately manifests as a larger area of ​​liquid crystal domain morphology.

[0036] Adding a very low content of NTCDA helps to improve the BDS of liquid crystal epoxy. BGE-0.4 can reach 117.04kV / mm (thickness of the film sample is 100±5μm), which is 11.28% higher than that of BGE-0. Thanks to the semiconductor properties of the NTCDA molecule, the LUMO energy level of the NTCDA molecule is lower than that of the liquid crystal epoxy matrix. The introduction of the NTCDA strategy effectively delays the occurrence of electrical breakdown by constructing an energy band difference to capture high-energy electrons. However, if the NTCDA doping level continues to increase, a conductive path will be formed inside the material, resulting in a sudden drop in the BDS after exceeding a certain doping threshold.

[0037] Compared with BAE-0 and BGE-0, the high-temperature BDS of BAE-0.1~0.7 and BGE-0.1~0.7 have been greatly improved. The BDS of BGE-0.4 at 200℃ is only reduced by 13.55% compared with that at room temperature, and the BDS of BAE-0.7 at 200℃ is only reduced by 0.004% compared with that at room temperature.

[0038] Liquid crystal epoxy matrix itself has excellent heat resistance, and the introduction of NTCDA has almost no effect on Tg. The Tg of the film is greater than or close to 200℃, and can reach up to 221.7℃.

[0039] The thermal conductivity increases with the increase of NTCDA content. The thermal conductivity of BAE-1 is 0.469 W·m-1·K-1, which is about 60% higher than that of BAE-0; the thermal conductivity of BGE-1 is 0.544 W·m-1·K-1, which is about 96% higher than that of BGE-0. Thanks to the large number of liquid crystal domains produced by the crystallization effect of NTCDA, phonons are quickly conducted in the liquid crystal domains formed by the orientation of the polymer with almost no scattering, thereby improving the efficiency of heat energy transfer.

[0040] The value of x in BAE-x or BGE-x includes any one of 0%, 0.1%, 0.4%, 0.7% and 1%.

[0041] BAE-x is specifically a compound of BAE and NTCDA, and BGE-x is specifically a compound of BGE and NTCDA.

[0042] The present invention also provides a method for preparing an insulating and thermally conductive enhanced liquid crystal epoxy, comprising the following specific steps:

[0043] S1: Add the corresponding mass of NTCDA to 0.074g BGE or 0.166g BAE and sonicate, add 0.5g TMBP to the uniformly dispersed solvent, heat to 110°C, make TMBP completely molten and stir rapidly for 5 minutes;

[0044] S2: Add 0.165g TMB, heat to 170℃, maintain the temperature and stir rapidly for 3 minutes, place the molten liquid in a vacuum box at 140℃ for degassing for 5 minutes, then inject it into the mold and place it in a drying oven for curing. The first stage is cured at 140℃ for 4h, the second stage is heated to 180℃ for curing for 4h, and the final stage is heated to 200℃ for curing for 2h.

[0045] The BGE system in S1 was sonicated at room temperature.

[0046] The BAE system in S1 was sonicated at 70°C.

[0047] The cross-linking principle of liquid crystal epoxy matrix and the liquid crystal induction mechanism of NTCDA are shown in Figure 1 a. It should be noted that the added BGE or BAE does not participate in the formation process of liquid crystal domains (the purpose of adding BGE or BAE is twofold: one is to serve as a solvent for NTCDA to ensure that NTCDA is evenly dispersed in the liquid crystal epoxy matrix; the other is that due to the large number of rigid molecules in the liquid crystal epoxy, the mechanical properties of the cured sample are very poor and the material is very brittle. Adding a small amount of BGE or BAE can supplement the mechanical properties of the material)

[0048] Example 2: Under a polarized light microscope (POM), the thin film prepared in the present invention, BGE-0 without adding NTCDA, has shown a good smectic phase liquid crystal domain morphology, which is in the form of spherulites with a diameter of 5 to 20 μm. Figure 1 b and 1c, BGE-0 benefits from the self-assembly of the π-π interaction between the biphenyl crystal units in the monomer and the curing agent, constructing a mesomorphic supramolecular ordered structure. The introduction of NTCDA changes the mesomorphic conformation, showing a needle-like liquid crystal domain morphology. At the same time, with the increase of NTCDA content in the matrix, the content of liquid crystal domains in the film continues to increase significantly. The changes in the crystal phase and number of liquid crystal domains are attributed to the different forms of intermolecular interactions generated after the introduction of NTCDA, see Figure 1 dg, here the BGE system is used as an example for explanation, the BAE system has similar results, the order of the liquid crystal can not only be established by the intrinsic liquid crystal ordering effect in the matrix, but also can be rapidly enhanced by mixing with a properly proportioned dopant, in view of the low content of NTCDA can induce the appearance of large-area liquid crystal domains, such a significant induction effect makes NTCDA used as a liquid crystal inducing agent to be studied in the present invention;

[0049] When NTCDA is added into the melt of liquid crystal epoxy matrix, the light yellow transparent solution immediately turns black within a few seconds. Figure 2 a. Due to the charge transfer interaction, an electron donor-acceptor complex (EDA) is formed. The electron transition forms a new charge transfer absorption band, which changes the light absorption characteristics. From the perspective of molecular structure, NTCDA is rich in carbonyl electron-attracting groups and has the ability to accept electrons; the aromatic compound TMBP and the aromatic amine TMB, especially the amino group on the TMB molecule, are electron-rich and tend to donate electrons. Using the simulation method of the Dmol3 module of Materials Studio, it is calculated that the LUMO energy level of NTCDA is low, while the HOMO energy levels of TMBP and TMB are high, the electron transition barrier is small, and electrons are more likely to escape transition, which is a prerequisite for the formation of EDA. Figure 2 b.

[0050] To confirm the formation of EDA, the fluorescence characteristics of EDA were used to detect the fluorescence spectra of bimorphic liquid crystal epoxy matrix, NTCDA, and BGE-1 melt. Figure 2 c. Under the excitation of light of a specific wavelength, electrons are transferred from the donor to the acceptor to form an excited state. When the excited electrons return to the ground state, they release energy, which is expressed in the form of fluorescence. NTCDA (named "NTCDA"), bimorph liquid crystal epoxy (named "LCE"), and BGE-1 melt (named "EDA") were prepared with BGE to make solvents of appropriate concentrations for fluorescence spectrum testing at an excitation wavelength of 320nm. Fluorescence peaks appeared at 390nm, which is the emission spectrum peak of the BGE solvent. The BGE solvent sample of BGE-1 (EDA-em-320ex) showed a unique fluorescence peak at 612nm, which is the emission spectrum peak of EDA caused by charge transfer interaction, confirming the existence of EDA. At the same time, when the BGE-1 melt, BGE-0, and BGE-1 films were directly irradiated with 395nm ultraviolet light, the BGE-0 film did not show fluorescence, while the BGE-1 melt and film showed fluorescence. The film fluorescence can be seen Figure 2 d, proving that the introduction of NTCDA produces EDA. The use of 395nm ultraviolet light for testing avoids the fluorescence effect of BGE solvent, that is, the fluorescence phenomenon in the system is only caused by EDA.

[0051] The charge transfer effect in the EDA formation process enhances the intermolecular attraction and significantly improves the orderliness of the liquid crystal domains. At the same time, the naphthalene ring of NTCDA has a stronger conjugation effect and a more uniform electron cloud distribution than the biphenyl group, so it has a larger conjugated adsorption energy, which promotes a more orderly stacking of rigid groups. The synergistic effect of charge transfer and conjugated bond energy makes the NTCDA dopant act as a liquid crystal promoter. We explore the liquid crystal enhancement mechanism of NTCDA from two aspects of simulation and experimental characterization. Molecular dynamics (MD) simulation is used to simulate the radial distribution function ( RDF) simulation was performed to characterize the local arrangement and order of the molecules in terms of structure. The O atom on the same plane as the mesogenic unit was taken as the reference particle. The RDF calculation was performed on the molecular dynamics model at room temperature and 200℃ (473K). r is the distance between the O atom on the same plane as other mesogenic units and the reference particle. All O atoms in the model are connected to the mesogenic unit. The position of the O atom can represent the position of the mesogenic unit to a certain extent. The g(r) peak represents the response signal of the mesogenic unit at this time. At room temperature, both models have multiple periodic characteristic peaks arranged in layers, see Figure 3 a, that is, there are multiple adsorption layers, which verifies the orderly arrangement of molecules of BGE-0 and BGE-1. The peak value appears at the same position, and BGE-1 Peaks appear at the same position, and the distance between the mesogens in BGE-1 is smaller. It can be judged that the mesogens have stronger adsorption force after the introduction of NTCDA, which greatly promotes the construction of liquid crystal domains. The model is subjected to molecular dynamics at 473K and RDF calculation is performed. Figure 3 b. Both BGE-0 and BGE-1 still maintain highly ordered periodic arrangement at high temperatures, and BGE-1 still has a higher π-π force between mesogens at high temperatures, which may provide support for the material's heat resistance and the stability of its electrical properties at high temperatures. The classical force field in the MD simulation process is based on empirical atomic motion and does not consider electronic behavior. Therefore, the adsorption force in this simulation is completely provided by the conjugated bond π-π force;

[0052] Although NTCDA is difficult to directly participate in the cross-linking reaction, it can stably exist in the molecular gap at the end of the epoxy cross-linking chain due to its stronger conjugation effect, more uniform electron cloud distribution and flattened configuration. Its existence form is also diverse. Several typical molecular segments in the cross-linking model are selected, see Figure 4 a and 4b, the crystallographic unit spacing and conjugated binding energy of biphenyl-biphenyl and naphthalene-biphenyl are calculated, see Figure 4c. Regardless of whether one NTCDA molecule or multiple NTCDA molecules are inserted into the gap between biphenyl elements, the distance between naphthalene and biphenyl is always smaller than that between biphenyl and biphenyl. When only one NTCDA molecule is inserted, the simulated value of the distance between naphthalene and biphenyl is Compared with biphenyl-biphenyl, it is reduced by 8.6%. At the same time as the spacing is reduced, it is found that the adsorption energy of naphthalene-biphenyl is increased by 41.4% compared with biphenyl-biphenyl, which proves that the molecular filler NTCDA adjusts the order inside the liquid crystal epoxy by reducing the molecular spacing and increasing the binding energy.

[0053] Example 4: In order to further explore the molecular stacking mode of liquid crystal domains and the crystallization mechanism of NTCDA, we conducted wide angle X-ray scattering (WAXS) analysis of BGE-0 and BGE-1 samples. Figure 4 d. After doping with NTCDA, the distance between mesogen molecules is significantly reduced. Reduce to The result that NTCDA makes molecules more compact is consistent with the trend of MD simulation. Figure 4 e and 4f, the scattering ring of BGE-1 is darker and clearer than that of BGE-0, which is caused by the difference in the internal structures of the two films. The scattering intensity of X-rays in certain positions in BGE-1 is stronger, reflecting that the π-π stacking between the crystallization units in BGE-1 is more highly ordered; after exploring the NTCDA crystallization method, the electrothermal properties of the liquid crystal film are characterized and analyzed in this invention. First, according to the cumulative probability function of the Weibull distribution, the BDS and shape parameter β of the liquid crystal epoxy are obtained. β reflects the breakdown stability of the liquid crystal epoxy. Adding extremely low content (≤0.4%) of NTCDA helps to improve the BDS of the liquid crystal epoxy. BGE-0.4 can reach 117.04kV / mm, which is 11.28% higher than the BDS of BGE-0. Figure 5 a and 5c. The LUMO energy level of the NTCDA molecule is lower than that of the liquid crystal epoxy matrix. The introduction of the NTCDA strategy captures high-energy electrons by constructing an energy band difference, effectively delaying the occurrence of electrical breakdown. This can be verified by partial discharge testing. After applying an AC voltage to the sample, some high-energy electrons of BGE-0.4 have been captured, so it has a lower partial discharge amount under the same voltage and a lower probability of breakdown. In addition, the hindering effect of rigid liquid crystal domains on high-energy electrons and the electron capture effect of aromatic groups (naphthalene rings, biphenyl groups) have a synergistic and positive effect on the improvement of BDS.

[0054] However, the BDS of BAE-0.1 and BAE-0.4 did not show an improvement effect. Figure 5b and 5c, due to the high viscosity of BAE and other issues, the dispersion of NTCDA is poor, and liquid crystal aggregation occurs. Their POM images verify this. The crystalline and amorphous regions show different insulation properties, which ultimately leads to BDS not meeting expectations. As a molecular semiconductor, when NTCDA is introduced at a high content, a conductive path is formed in the matrix under the action of the electric field, which reduces the insulation properties of the material. Through MD simulation, the free volume parameter of BAE / BGE-1 is slightly increased, see Figure 5 d, the electron free path increases, which also leads to a decrease in BDS.

[0055] Compared with BAE-0 and BGE-0, the high temperature BDS of BAE-0.1~0.7 and BGE-0.1~0.7 has been greatly improved. The BDS of BGE-0.4 at 200℃ is only 13.55% lower than that at room temperature, and the BDS of BAE-0.7 at 200℃ is only 0.004% lower than that at room temperature. This result is surprising. Figure 6 In order to explore the high temperature insulation mechanism under the action of NTCDA, the glass transition temperature (Tg) of some samples was first characterized by DSC and MD simulation. Figure 7 ad, the liquid crystal epoxy matrix itself has excellent heat resistance, and the introduction of NTCDA has almost no effect on Tg. The Tg of the film is greater than or close to 200°C, and the highest can reach 221.7°C. The Tg of the film was not exceeded during the high-temperature BDS test, that is, the polymer chain end remained stable and there was no change in the material state. This is the key to the film's high-temperature insulation properties. The thermal conductivity of the sample was characterized, see Figure 7 e and 7f, the thermal conductivity increases with the increase of NTCDA content. The thermal conductivity of BAE-1 is 0.469W·m-1·K-1, which is about 60% higher than that of BAE-0; the thermal conductivity of BGE-1 is 0.544W·m-1·K-1, which is about 96% higher than that of BGE-0. Thanks to the large number of liquid crystal domains generated by the crystal-inducing effect of NTCDA, phonons are quickly conducted in the liquid crystal domains formed by the orientation of the polymer without scattering, thereby improving the efficiency of heat energy transfer. Under the action of the electric field, the heat accumulated by the electron attack and the heat of the environment are effectively conducted in the high thermal conductivity film, which effectively delays the occurrence of thermal breakdown;

[0056] In order to verify the effect of NTCDA mentioned in the above embodiment on capturing electrons by utilizing the energy band difference with the liquid crystal matrix, we conducted a TSDC test to characterize the trap energy level parameters. The experimental data and fitting curve of TSDC are shown in Figure 8 a and Figure 8As shown in b, the trap energy level can be calculated based on the depolarization current curve. The peak currents of BGE-0 and BGE-0.7 appear near 219°C and 227°C, respectively. The changes in the properties of their molecular chains near Tg often cause significant changes in electronic properties. The trap energy levels of these two samples were calculated. The trap energy level of BGE-0 is 1.32eV, while the trap energy level of BGE-0.7 is 2.68eV, which means that the introduction of NTCDA increases the trap energy level of the material. NTCDA creates a larger trap energy level and a stronger trap effect, making it difficult for carriers trapped in the trap to escape, resulting in a decrease in carrier mobility and an increase in breakdown strength.

[0057] The dielectric frequency dependence of BAE / BGE-x was characterized, see Fig. 9 a and 9b. With the increase of NTCDA content, the dielectric constant (εr) of BAE / BGE-x increases, indicating that its polarization strength increases. NTCDA molecules are rich in carbonyl polar groups. The introduction of carbonyl groups improves the dielectric response of the material, and the resulting EDA complex is more easily polarized under an external electric field, thereby increasing εr. At the same time, NTCDA modification leads to more space charges inside the material, and the movement and redistribution of space charges under the electric field will also contribute to εr. It is noted that the dielectric loss (tanδ) of BAE / BGE-1 increases at high frequencies (103Hz). The reasons for this phenomenon are analyzed. On the one hand, due to the occurrence of dipole polarization, the response of polar groups at high frequencies cannot keep up with the changes in the electric field, resulting in increased energy dissipation and thus an increase in tanδ. On the other hand, due to the occurrence of conductivity loss, EDA can separate and release carriers during its formation. At the same time, the introduction of NTCDA can change the band structure of the matrix, making the generation and migration of carriers easier. Therefore, liquid crystal epoxy modified with a high content of NTCDA has more carriers, and the migration of carriers under a high-frequency electric field ultimately leads to an increase in conductivity loss.

[0058] Therefore, the present application proposes a solution to the disadvantages that still exist in liquid crystal epoxy. The molecular filler NTCDA is modified to improve the performance of liquid crystal epoxy. NTCDA has intrinsic molecular semiconductor properties. The introduction of a specific trace amount of NTCDA can improve the insulation properties and high-temperature insulation properties of the material. In addition, the unique liquid crystal inducing agent properties exhibited by NTCDA in the present invention achieve a further significant improvement in the thermal conductivity of liquid crystal epoxy.

[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An insulating and thermally conductive enhanced liquid crystal epoxy, characterized in that: include: Liquid crystal epoxy, wherein a thin film is arranged inside the liquid crystal epoxy; The film comprises: any one of BAE-x and BGE-x films, wherein x represents the doping amount of NTCDA; The liquid crystal epoxy matrix generates a charge transfer interaction with NTCDA and forms an electron donor acceptor complex (EDA).

2. The insulating and thermally conductive enhanced liquid crystal epoxy according to claim 1, characterized in that: The value of x in the BAE-x or BGE-x includes any one of 0%, 0.1%, 0.4%, 0.7% and 1%.

3. The insulating and thermally conductive enhanced liquid crystal epoxy according to claim 1, characterized in that: The BAE-x is specifically a compound of BAE and NTCDA, and the BGE-x is specifically a compound of BGE and NTCDA.

4. A method for preparing an insulating and thermally conductive enhanced liquid crystal epoxy, applied to the insulating and thermally conductive enhanced liquid crystal epoxy according to any one of claims 1 to 3, characterized in that: The specific steps include: S1: Add the corresponding mass of NTCDA to 0.074g BGE or 0.166g BAE and sonicate, add 0.5g TMBP to the uniformly dispersed solvent, heat to 110°C, make TMBP completely molten and stir rapidly for 5 minutes; S2: Add 0.165g TMB, heat to 170℃, maintain the temperature and stir rapidly for 3 minutes, place the molten liquid in a vacuum box at 140℃ for degassing for 5 minutes, then inject it into the mold and place it in a drying oven for curing. The first stage is cured at 140℃ for 4h, the second stage is heated to 180℃ for curing for 4h, and the final stage is heated to 200℃ for curing for 2h.

5. The method for preparing an insulating and thermally conductive enhanced liquid crystal epoxy according to claim 4, characterized in that: The BGE system in S1 is subjected to ultrasound at room temperature.

6. The method for preparing an insulating and thermally conductive enhanced liquid crystal epoxy according to claim 4, characterized in that: The BAE system in S1 was sonicated at 70°C.